2022
DOI: 10.3390/s22124501
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Needs in the Fields of Artificial Intelligence, Internet of Things and Edge Computing

Abstract: Industry 4.0 corresponds to the Fourth Industrial Revolution, resulting from technological innovation and research multidisciplinary advances. Researchers aim to contribute to the digital transformation of the manufacturing ecosystem both in theory and mainly in practice by identifying the real problems that the industry faces. Researchers focus on providing practical solutions using technologies such as the Industrial Internet of Things (IoT), Artificial Intelligence (AI), and Edge Computing (EC). On the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 47 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…They found that systems that integrate IoT technology and AI performed excellently in enhancing students' creative experiences and learning outcomes [38]. Ma 2022) provided practical case studies and data support through empirical research on students using IoT technology to learn art [44]. In summary, the research of these scholars offered a strong theoretical basis for this study, supporting the innovative application of integrating IoT technology and AI in art education.…”
Section: Literature Reviewmentioning
confidence: 72%
“…They found that systems that integrate IoT technology and AI performed excellently in enhancing students' creative experiences and learning outcomes [38]. Ma 2022) provided practical case studies and data support through empirical research on students using IoT technology to learn art [44]. In summary, the research of these scholars offered a strong theoretical basis for this study, supporting the innovative application of integrating IoT technology and AI in art education.…”
Section: Literature Reviewmentioning
confidence: 72%
“… ensured the possibility of using an identical basing system at each station, which has a positive impact on the final quality of the product,  reduced the cost of manufacturing basing systems due to their unification,  provided the possibility to carry out the process on two work stations,  ensured optimum use of production space,  reduced costs of manufacturing the machine due to the relatively low manufacturing costs of the transport system built from modular systems. The implemented innovative design solution of the transport system based on pneumatic drives is an example of the possibility to use simple and low-cost drives to perform important tasks in automated production lines operating within the framework of Industry 4.0 (Stadnicka, et al, 2022) (Kolberg & Zuhlke, 2015) (Brzozowska & Gola, 2021). The presented solution is the result of the search for optimal process execution conditions, which is one of the basic activities while designing robotic production systems.…”
Section: Discussionmentioning
confidence: 99%
“…This assembly is driven by a pistonless cylinder (8), which, thanks to its equipment, makes it possible to set precisely the drive stroke. The container is gripped during transport by movable arms (9), which are rotated by the cylinder (10). The tank between the arms is blocked in place with the use of clamping cylinders (11) (Fig.…”
Section: Technical Solutionsmentioning
confidence: 99%
“…or which can facilitate the achievement of the same, also fall within the Industry 4.0 paradigm. Some examples are the industrial internet [40], integrated industry [41], the factory of the future [42,43], Smart Industry and Smart Manufacturing [44][45][46][47], and many other emerging technologies.…”
Section: Influence Of Contemporary Technologies On the Sustainability...mentioning
confidence: 99%